(untitled) (Albayan Scientific Journal, 2023)
This work aimed to explore the most important interrelations between the topographical features and some chemical and physical characteristics, their extent as well as interactions with saturated hydraulic conductivity. To carry out this work, considering the complex variation of the Al Jabal Alkhadar topography seven soil samples were collected from the surface layers of the most important soil orders. This study asserted that the topography has an indirect role in creating spatial variability of the physical properties, for its control in the spatial distribution of rain and temperature range, thus weathering processes, which its products define the classes of textures, the most responsible for controlling the physical and chemical behavior of soil, where we may achieve this responsibility to its sand and clay fractions. It was found that the negative effects associated with the dominance of sodium cations on exchangeable complex, and the consequent reduction in saturated hydraulic conductivity rates, is conditioned by the abundance of the clay fraction. This is rare under dry and semi-dry climatic conditions that impose the rule of physical weathering and thus its tendency to roughness. For this reason, relations of mutual sodium ratios with the coefficient of saturated hydraulic conductivity were characterized by high levels of significance. This is a result of the direct relationship between the sandy joint and the degree of alkalinity. Whereas, the organic matter had negative relations with the saturated hydraulic conductivity coefficient as a result of the underlying relationship between the slurry and the organic content, and thus an extension of the negative relationships between the clay content with the hydraulic conductivity coefficient.